ANALYSIS OF TRUST AND SERVICE QUALITY TOWARDS LOYALTY WITH SATISFACTION AS INTERVENING VARIABLE ON BNI MOBILE BANKING CUSTOMERS AT PT. BNI UNITOMO CASH OFFICE SURABAYA - Intan Permatasari; Eko Purwanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study was to analyze the effect of trust and quality of mobile banking services on loyalty and to analyze the effect of customer satisfaction on customer loyalty mediated by mobile banking service satisfaction. This research was conducted on consumers of PT. BNI Unitomo Cash Office Surabaya. The population is customers who use mobile banking. While, the sample is 100 people with proportional random sampling. The type of data used is quantitative data. Data collection techniques using questionnaires, observation and literature study. Data were analyzed using path analysis using Smart PLS 3rd version for windows. The conclusion from the research shows that trust has no positive and significant effect on loyalty, while trust through customer satisfaction has a positive and significant effect on loyalty. Furthermore, the quality of mobile banking services has a positive and significant effect on loyalty either through customer satisfaction or directly Keywords: Trust, Service Quality, Customer Satisfaction, Loyalty